Incentivizing teamwork to promote sustainability - Kathleen Segerson (Proceedings of the National Academy of Sciences, 2025)
There are a variety of contexts in which “pitching in” to address environmental or resource management problems could benefit from individuals or firms working not just on their own but also working together collaboratively as a group. Examples include working together on promoting conservation or habitat protection, the sharing of information, or the development of less polluting products or production processes. However, to date, the literature on environmental policy has considered only the incentives for individual parties (e.g., firms, landowners, or individuals) to take steps (i.e., exert “effort”) to reduce pollution or meet resource management goals where those steps impact that party’s own environmental footprint or performance. Missing from the literature is any consideration of the ability of one party to undertake activities that instead help another improve the latter’s performance. Such help could be either a substitute for or a complement to one’s own effort. This paper presents an analysis showing that traditional policy approaches based on individual performance cannot generally efficiently incentivize both effort and help, but a (properly designed) collective approach where rewards or punishments are based on group performance can. This suggests an additional rationale for the use of collective approaches as a potentially important tool for promoting sustainability that has not been recognized in the literature.